Neutrophils—From Bone Marrow to First-Line Defense of the Innate Immune System - Kraus, Richard Felix; Gruber, Michael Andreas (Frontiers in Immunology, 2021)
Neutrophils (polymorphonuclear cells; PMNs) form a first line of defense against pathogens and are therefore an important component of the innate immune response. As a result of poorly controlled PMN activation, however, PMNs can also mediate tissue damage in infectious or autoimmune diseases. According to current knowledge, PMNs are part of the pathogenesis of numerous diseases. Scientific advances in the past two decades have changed the role of neutrophils from that of solely immune defense cells to cells that are responsible for the general integrity of the body, even in the absence of pathogens. To better understand PMN function in the human organism, our review outlines the role of PMNs within the innate immune system. This review provides an overview of the migration of PMNs from the vascular compartment to the target tissue as well as their chemotactic processes and illuminates crucial neutrophil immune properties at the site of the lesion. The review is focused on the formation of chemotactic gradients in interaction with the extracellular matrix (ECM) and the influence of the ECM on PMN function. In addition, our review summarizes current knowledge about the phenomenon of bidirectional and reverse PMN migration, neutrophil microtubules, and the microtubule organizing center in PMN migration. As a conclusive feature, we review and discuss new findings about neutrophil behavior in cancer environment and tumor tissue.